(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Different methods to control flax diseases are admissible in the modern plant protection. It is advised to treat seeds and growing plants by fungicides to kill the pathogens of fungal diseases. Fertilisation by microelements and using of right means of agrotechnology (optimal sowing time, resistant varieties etc.) are preventing plants from physiological injures. However, one of the most effective means against diseases is development and growing of resistant varieties.Fibre flax breeding has been carried out in Lithuania since 1922 in Dotnuva Plant Breeding Station. Since 1965 this work is being done in Upyte Research Station.In this paper we analyse a fibre flax collection in Upyte Research Station and show that some varieties are resistant to most widespread flax fungal diseases.